POLA PENGELOLAAN PASRAMAN NON FORMAL PASIR UKIR DI DESA PEDAWA, KECAMATAN BANJAR, KABUPATEN BULELENG (KAJIAN MANAJEMEN PENDIDIKAN HINDU) - Komang Trisna Mahartini (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
This study aims to determine (1) the management pattern of Pasraman Non Formal Pasir Ukir; (2) constraints faced in the management of the non-formal Pasraman Pasir Ukir; and (3) efforts to overcome obstacles in the management of Pasraman Non Formal Pasir Ukir in Pedawa Village, Banjar District, Buleleng Regency. The research method used is descriptive qualitative. The instruments used were the researchers themselves, interview guides, recording devices, writing instruments, and a number of other tools. The findings indicate that there are activities for the management of Pasraman Non Formal Pasir Ukir namely (1) planning (2) organizing; (3) staffing; (4) leading; and (5) controlling. The constraints faced in managing Pasraman are the implementation of the pasraman work program and human resources (managers, instructors, and students) as well as the social environment of the pasraman which greatly influences efforts in achieving goals. Efforts to overcome obstacles in the management of the non-formal Pasraman Pasir Ukir are optimizing the implementation of the pasraman program and empowering human resources and the social environment of the Pasraman in order to achieve the stated educational goals.